An introduction to spillover effects in cluster randomized trials with noncompliance. (August 2022) - Keele, Luke; Kang, Hyunseung
In some cluster randomized trials, subjects may not comply with their assigned treatment status. Such treatment noncompliance can create opportunities for spillover effects within clusters. Little research has focused on what can be learned in such context. This article provides a non-technical review of recent work on the complications that arise in cluster randomized trials where some units within treated clusters do not comply with treatment but the treatment spillovers over to these units. We motivate concepts using a hypothetical vaccine cluster randomized trial. We review that standard instrumental variable methods cannot recover the complier average causal effect in the presence of these spillovers. In fact, we review that without additional assumptions, little can be learned about compliance effects or spillover effects. We discuss one additional assumption that allows for bounds on a key causal effect. We also outline an estimator for these bounds.